Electrochemiluminescence Platforms Based on Small Water‐Insoluble Organic Molecules for Ultrasensitive Aqueous‐Phase Detection. (27th March 2019) - Han, Zhengang; Yang, Zhaofan; Sun, Heshui; Xu, Yali; Ma, Xiaofang; Shan, Duoliang; Chen, Jing; Huo, Shuhui; Zhang, Zhen; Du, Peiyao; Lu, Xiaoquan
Abstract: Highly efficient detection in the aqueous phase for water‐insoluble organic molecule probes is challenging. The bright aggregated‐state electrochemiluminescence (ECL) of 1, 1‐disubstituted 2, 3, 4, 5‐tetraphenylsiloles by a co‐reactant approach was discovered, and a heterogeneous aggregation‐induced emission ECL (HAIE‐ECL) was constructed at the electrode surface, showing very high ECL efficiency (37.8 %) and selective recognition for industrially important DNBP plasticizer with a low detection limit of 0.15 nm in the water phase. A mechanistic study indicates that ECL is mainly generated due to the high electron affinity of siloles and restriction of the intramolecular motions caused by their propeller‐like noncoplanar structures. This system realizes the sensing of organic‐based ECL in the water phase by solving the crucial problems of water insolubility and aggregation‐caused quenching (ACQ), and demonstrates potential for further application because of its design and high efficiency.